Lebanese banks’ state of readiness to lift banking secrecy - Ghinda Y. HAMDAR (Proche-Orient Études en management, 2018)
This paper aims to explore the level of readiness of Lebanese banks to adaptto a change highlighted by the international financial wave of transparency thatoppresses banking secrecy worldwide.